2012
DOI: 10.1016/j.molcel.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Independence of Repressive Histone Marks and Chromatin Compaction during Senescent Heterochromatic Layer Formation

Abstract: SUMMARY The expansion of repressive epigenetic marks has been implicated in heterochromatin formation during embryonic development, but the general applicability of this mechanism is unclear. Here we show that nuclear rearrangement of repressive histone marks H3K9me3 and H3K27me3 into nonoverlapping structural layers characterizes senescence-associated heterochromatic foci (SAHF) formation in human fibroblasts. However, the global landscape of these repressive marks remains unchanged upon SAHF formation, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
286
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(331 citation statements)
references
References 49 publications
44
286
1
Order By: Relevance
“…For example, the repressive mark H3K27me3 has been reported to associate with early to mid replication and with early and mid origins (Chandra et al, 2012;Julienne et al, 2013;Picard et al, 2014), as well as with late replication (Thurman et al, 2007). In our data, peaks of H3K27me3 appear to follow two different patterns.…”
Section: Replication Timing In Relation To Chromatin Packagingmentioning
confidence: 42%
“…For example, the repressive mark H3K27me3 has been reported to associate with early to mid replication and with early and mid origins (Chandra et al, 2012;Julienne et al, 2013;Picard et al, 2014), as well as with late replication (Thurman et al, 2007). In our data, peaks of H3K27me3 appear to follow two different patterns.…”
Section: Replication Timing In Relation To Chromatin Packagingmentioning
confidence: 42%
“…However there are mainly two lines that stand out from the block of active marks in the hierarchical clustering dendrogram in Figure 1. One of these lines corresponds to the polycomb (Pc) associated repressive chromatin marks H3K27me3 characteristics of the so-called facultative heterochromatin (Barski et al 2007;Chandra et al 2012). This is the only mark that anti-correlates with most of the active marks except H4K20me1.…”
Section: Combinatorial Analysis Of Chromatin Marks At Human Gene Prommentioning
confidence: 99%
“…1,2 The known causes of cellular senescence include telomere shortening, oxidative stress, DNA damage and hyperoncogenic signaling. 3 H-RasV 12 has been used as a model to induce senescence in normal cells. [4][5][6] Senescent cells are typically characterized by a large flat morphology and the expression of a senescence-associated β-galactosidase activity (SA-β-gal), and nuclei of senescence cells may remodel to form the heterochromatin structures termed the senescenceassociated heterochromatin foci (SAHF).…”
mentioning
confidence: 99%
“…7,[9][10][11] Recently, it has been shown that repressive markers, such as H3K9me3, H3K9me2 and H3K27me3, are rearranged into the nonoverlapping structural layers in SAHF. [12][13][14] Changes of heterochromatin organization generate a repressive chromatin environment that prevents transcription of genes that promote growth, thereby stabilize the state of senescence. 7,15 The retinoblastoma (RB) tumor suppressor is an important senescence regulator, which is typically activated during senescence and enforces the expression of other senescence-inducing proteins.…”
mentioning
confidence: 99%